Effect of Current Strength and Flow Rate of Shielding Gas on the Impact and Tensile Strength of GMAW Welsing Result on SPHC Materials - Radhi Nurvian Amrullah; Subagiyo (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
GMAW welding is one of the welds that is easy to use, especially for welding low-carbon steel that is generally widely used in the process of making frame structures, an example is a car frame which is generally made using materials that have strong, ductile, lightweight, and able to withstand impact and tensile loads when the car is used, one example of the material is SPHC. The problem is that GMAW welding results are affected by welding parameters. In this study, the parameter chosen was the strong variation of the welding current. The purpose of this study is to determine the strong influence of the current and flow rate of protective gases as well as the interaction on the impact and tensile strength of GMAW welding results on SPHC materials. This study used an experimental method with current strength parameters worth 120A,130A, and 140A as well as variations in the flow rate of protective gases, namely 15 liters/minute,20 liters/minute, and 25 liters/minute. The results of research in general, the impact strength on the weld metal has a lower result than the row material, and the tensile strength on the weld metal has a higher yield than the row material. From the study, it can be seen that the optimal current strength and flow rate of protective gas is a current strength of 140 A and a flow rate of protective gas worth 25 L /minute with an impact strength of 2.91 J/mm2 and a tensile strength of 431.72 MPa.